Comparative anatomy and histochemistry between the wood of medicinal market samples of guayacan and that of Guaiacum coulteri A. Gray - Centeno-Betanzos, Lucía Yoscelina; Brechú-Franco, Alicia Enriqueta; Osuna-Fernández, Helia Reyna; Laguna-Hernández, Guillermo; León-Gómez, Calixto (Instituto de Ecología, A.C., 2013)
The medicinal plant guayacan is recommended for health problems derived from diabetes mellitus. The species most often associated in the literature with the common name guayacan is Guaiacum coulteri. For this study, anatomical and histochemical comparisons were made of wood samples from five markets in Mexico City and of Guaiacum coulteri wood deposited in the xylarium MEXUw, housed at the Instituto de Biología, Universidad Nacional Autónoma de México. The market samples were anatomically dissimilar, not only to Guaiacum coulteri but also to each other. The histochemical comparison showed higher lipid and glucoprotein contents in the parenchyma of the market samples than in G. coulteri, whose parenchyma is scarce. These results demonstrate the importance of anatomical characterization of species that are commercialized for medicinal use in order to assure an accurate identification. The histochemical reactions of samples enabled the structural differences among them to be observed with greater precision, and provided more information on their cellular composition; however, these results could be complemented with a subsequent phytochemical study that would provide more information on the compounds in each sample.